Personality dimensions in schizophrenia: A family study. (May 2017) - Goghari, Vina M.
Abstract: Studies have demonstrated that personality traits differ in schizophrenia patients and family members compared to controls, suggesting familial risk. This study evaluated personality traits in a family study of schizophrenia, as well as the relationship between personality traits and symptoms and social functioning in schizophrenia patients. Thirty-two schizophrenia patients, 28 adult non-psychotic relatives, and 27 community controls completed the Dimensional Assessment of Personality Pathology–Basic Questionnaire (DAPP-BQ). Schizophrenia patients differed on many dimensions of the DAPP-BQ compared to controls and/or relatives: affective lability, anxiousness, callousness, conduct problems, cognitive dysregulation, identity problem, intimacy, insecure attachment, low affiliation, narcissism, oppositionality, restricted expression, self-harm, submissiveness, and suspiciousness. No differences were found between relatives and controls. Furthermore, in schizophrenia patients, associations were found between personality and particularly general symptoms, as well as social functioning. Personality traits can be conceptualized as an extended phenotype in schizophrenia patients. Highlights: Schizophrenia patients differed on many personality traits compared to controls and relatives. Non-psychotic relatives did not significantly differ from controls on any personality trait. Personality was related to symptoms and functioning in schizophrenia.